Association between school bullying experience and work-related subjective well-being: A systematic review - Mai Iwanaga; Mako Iida; Natsu Sasaki; Risa Kotake; Yasuko Morita; Hiroki Asaoka; Kyosuke Nozawa; Hiroo Iwanaga; Norito Kawakami (Environmental and Occupational Health Practice, 2023)
Objectives: Work-related subjective well-being (SWB) may be negatively affected by early-life adverse experiences, such as school bullying experience. This study aimed to identify the association between work-related SWB and school bullying experiences. Methods: A systematic review was conducted using five electronic databases to search for published observational studies from inception to May 5th, 2022. Eligibility criteria included the original papers in English, which measured school bullying experiences and work-related SWB (eg, satisfaction, engagement). Eight researchers independently conducted screening and a full-text review. We used the Risk of Bias Assessment tool for Non-randomized Studies to assess the certainty of the evidence. Narrative data were summarized. The study has been registered at UMIN-CTR (UMIN000040513). Results: A total of 6,842 studies were initially searched. We included two cross-sectional studies. Both studies were rated as high risk for bias in exposure measurements and incomplete outcome data. These studies showed conflicting results. One study reported that school bullying was negatively associated with job satisfaction among British lesbian, gay, or bisexual workers; on the other hand, another study reported that school bullying was positively associated with work engagement among Japanese workers. Conclusions: We found limited inconsistent evidence for the association between work-related SWB and school bullying experiences.